Avaliação do método famacha© como critério de tratamento seletivo no auxílio à conservação da raça canindé - Góes, Sarah Diógenes Mendonça de Mattos Brito (Universidade Federal Rural do Semi-Árido, 2021)
One of the main obstacles to goat farming in Brazil is the economic losses caused by gastrointestinal parasites. That in addition to decreasing production, it also causes an increase in costs with anthelmintic applications for the control of parasites. To reduce this cost, the FAMACHA© method was developed, which consists of the individual assessment of each animal to determine the degree of anemia based on the level of infection by hematophagous parasites and make the decision whether the animal should be treated or not, reducing the selective pressure about the parasites. However, in locally adapted breeds, we can find adaptive physiological changes in which animals present clinical parameters different from animals of exotic breeds. Thus, the objective of this work was to evaluate the effectiveness of the application of the FAMACHA© method in goats of the Canindé breed, raised in an extensive system in the Brazilian semiarid region. For this, 161 Canindé breed goats were used, where the animals were clinically examined, and classified using the F© score in 5 categories, F©1, F©2, F©3, F©4 and F©5, where the animals were diagnosed as anemic (F©3,4 and 5 or F© 4 and5) or non-anemic (F© 1, 2 and 3 and F© 1 and 2). Blood samples were collected for complete blood count and hematocrit count, gold standard for anemia detection, from each animal, stool collection was performed to count eggs per gram of stool (ECC) and stool culture to confirm the presence of H . contortus through the identification of its infective larva, in two periods of the year, dry and rainy. Given the data obtained, there were no significant differences between HTC and F© data between the analyzed periods, however, when evaluating the F©, it was observed that the mean of the animals' classification remained similar in the two periods, and anemia it was not confirmed in any animal by HTC, there was only a significant difference in the ECC count between the rainy and dry season, where in the latter, the animals presented a lower mean of ECC. Therefore, the study concluded that there is a contradictory relationship between the classification of anemia using the F© method, ECC and HTC values related to H. contortus infection, not suggesting the use of the F© method for Canindé goats and still proposing the elaboration of new HTC tracks associated with F© scores from 1 to 5
Keywords: Haemonchus contortus; Hematócrito; Caprinos nativos; Endoparasitoses; Resistência; Haemonchus contortus; Hematocrit; Native Goats; Endoparasites; Resistance; CIENCIAS AGRARIAS::MEDICINA VETERINARIA